2020
DOI: 10.1515/jpm-2020-0395
|View full text |Cite
|
Sign up to set email alerts
|

Educating future professionals in perinatal medicine: the attitude of medical and nursing students towards childbirth

Abstract: ObjectivesThe main objective of the present study was to evaluate what educational needs were being neglected in current perinatal educational program in the University of Malaga.MethodsWe performed a cross-sectional study using the Students’ questionnaire on attitudes towards childbirth (CAVE-st) in a sample of 378 students who were finishing their undergraduate or postgraduate academic perinatal program, including medical and nursing students.ResultsThe Cronbach’s alpha reliability coefficient was 0.895. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The questionnaire included an informed consent document, a brief explanation of the reasons why the research was being held, the questionnaire on attitudes towards childbirth (CAVE, acronym for "cuestionario de actitudes sobre vivencias y experiencias en el parto") [17,18], and a series of sociodemographic questions such as gender, age, city of residence and work, type of practice (public/private), and whether the participant had children. The survey was anonymized and included an authorization request for the subsequent analysis of the collected data.…”
Section: The Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire included an informed consent document, a brief explanation of the reasons why the research was being held, the questionnaire on attitudes towards childbirth (CAVE, acronym for "cuestionario de actitudes sobre vivencias y experiencias en el parto") [17,18], and a series of sociodemographic questions such as gender, age, city of residence and work, type of practice (public/private), and whether the participant had children. The survey was anonymized and included an authorization request for the subsequent analysis of the collected data.…”
Section: The Surveymentioning
confidence: 99%
“…In addition, content validity was undertaken by a Delphi panel of 16 experts, over 2 rounds. The validation process has already been published [17], and the scale has been used in previous studies [18]. The Spanish language validation resource showed that the questionnaire was a valid and reliable tool, with a Cronbach s alpha coefficient of 0.…”
Section: Instrumentmentioning
confidence: 99%